Cochrane Database of Systematic Reviews 2001
DOI: 10.1002/14651858.cd000361
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin for preventing infection in preterm and/or low-birth-weight infants

Abstract: Intravenous immunoglobulin for preventing infection in preterm and/or low birth weight infants (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 54 publications
4
58
0
4
Order By: Relevance
“…Previous trials with biological therapeutics, including intravenous immunoglobulins, anti-staphylococcal antibodies, and hematological growth factors, have failed to demonstrate clinically relevant improvement of sepsis rates and their routine therapeutic use is not recommended [21,22,51,[80][81][82]. A more detailed understanding of both the key protective and pathogenic pathways and the effects of GA on innate immunity will allow the development of new preventative and therapeutic strategies for neonatal infection.…”
Section: Potential Therapeutic Avenuesmentioning
confidence: 99%
“…Previous trials with biological therapeutics, including intravenous immunoglobulins, anti-staphylococcal antibodies, and hematological growth factors, have failed to demonstrate clinically relevant improvement of sepsis rates and their routine therapeutic use is not recommended [21,22,51,[80][81][82]. A more detailed understanding of both the key protective and pathogenic pathways and the effects of GA on innate immunity will allow the development of new preventative and therapeutic strategies for neonatal infection.…”
Section: Potential Therapeutic Avenuesmentioning
confidence: 99%
“…Data on the use of prophylactic IVIG appear mixed, with the majority of studies showing minimal benefit and questionable clinical utility. A 2013 Cochrane Review of 19 studies performed across 10 countries included preterm and/or low-birth weight infants and found IVIG was associated with a 3-4 % reduction in serious nosocomial infection and shorter duration of hospitalization (mean 2.1 days) but no benefit in infant mortality from infection [39]. Authors argue that this small but statistically significant reduction in infection should be weighed against the costs of broad recommendation across the large preterm infant population [39].…”
Section: Use Of Ivig Prophylaxis In Preterm Infantsmentioning
confidence: 99%
“…A 2013 Cochrane Review of 19 studies performed across 10 countries included preterm and/or low-birth weight infants and found IVIG was associated with a 3-4 % reduction in serious nosocomial infection and shorter duration of hospitalization (mean 2.1 days) but no benefit in infant mortality from infection [39]. Authors argue that this small but statistically significant reduction in infection should be weighed against the costs of broad recommendation across the large preterm infant population [39]. In contrast, animal studies have suggested potential detriment, showing that excessive IgG may impair microbial clearance [40,41].…”
Section: Use Of Ivig Prophylaxis In Preterm Infantsmentioning
confidence: 99%
“…The most recent Cochrane meta-analysis on the prophylactic administration of IVIG to prevent nosocomial infections included more than 5000 neonates from 19 studies (Ohlsson and Lacy, 2013a). When all studies were combined, a significant reduction in sepsis was noted (number needed to treat for an additional beneficial outcome was 33).…”
Section: Use Of Immunoglobulins In the Prevention Of Neonatal Sepsismentioning
confidence: 99%
“…There were no adverse events observed to be associated with the prophylactic use of IVIG. From a clinical perspective a 3e4% reduction in nosocomial infections without a reduction in mortality or other important clinical outcomes might be of marginal importance and has to be outweighed by the costs and the values assigned to the clinical outcomes (Ohlsson and Lacy, 2013a). This Cochrane review ended with the statement that there is no justification for further randomized trials testing the efficacy of previously studied IVIG preparations to reduce nosocomial infections in preterm and/or low birth weight infants.…”
Section: Use Of Immunoglobulins In the Prevention Of Neonatal Sepsismentioning
confidence: 99%